Facilitating Students’ Speaking Skill Achievement Using Self-Recorded Presentation - Sophia Binnendyk (International Journal of Education, Information Technology, and Others, 2021)
This article explores students’ speaking tasks, in the form of video presentation, employed by the teacher to facilitate students’ speaking skills during the online learning process. This paper also intends to describe students’ achievements resulted from the speaking task. An English teacher and her 11 students were chosen as the participants in conducting this study. This study applied a qualitative case study in which there are two kinds of the instrument to collect the data namely observation and questionnaires. The result showed that the students found some difficulties in conducting the task; however, their speaking skills increased, especially their vocabulary, pronunciation, and fluency.